Ultrathin wideband slot and patch FSS elements with sharp band edge characteristics - Krushna Kanth, V.; Raghavan, S. (International journal of electronics, 2020)
Two diverse applications of FSS as bandpass and bandstop filters with wideband and sharp band edge characteristics are investigated in this paper. The proposed design comprised of a tapered tripole element in aperture and patch type printed on either side of a dielectric material to act as bandpass and bandstop filters respectively. The structures are ultrathin in design; structures comprise two metallic layers, isolated by single thin substrates with a thickness of 0.027λ. In the case of bandpass, the structure shows a relative bandwidth (−1 dB) of 8.87% with insertion loss better than 0.2 dB at normal incidence. Whereas, in the case of bandstop, it shows 24.36% (−10 dB). Further, the parametric analysis is performed for obtaining optimal performance. Both structures in the proposed form have spectacular application in bandpass filtering (slot FSS) and electromagnetic shielding (patch FSS). Further, two design techniques are presented namely dielectric encapsulation and substrate integrated waveguide (SIW) based FSS structures to develop a periodic structure to cater the high power handling in microwave sources. Finally, a fabricated prototype along with experimental verification proves the validity of simulated results.